Longitudinal study of the stability of expresscd emotion in families of schizophrenic patients: A 9 - month folIow-up. - Pumar, Begoña; Santos, Asunción; Ayerbe, Ana; Espina, Alberto; García, Enrique; González, Pilar (The Spanish Journal of Psychology, 2001)
Sin resumen